Authentication of Identity Documents Using DNSSEC, Digital Signatures and QR Codes - Amaral, Luiz Fernando Ribeiro; Santos, Jorge Guilherme Silva dos; Rocha, Mateus Almeida; Gersch, Joseph; Amvame-Nze, Georges Daniel; Albuquerque, Robson de Oliveira; Sousa Júnior, Rafael Timóteo de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2017: Anais do XVII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2017)
This paper describes a system for authenticating identity documents by digitally signing the data and embedding it in a 2D code to be printed with the document. In the proposed scheme, a message is digitally signed using a digital signature block which is stored in a QR Code. The code is later scanned by the user and, after validation, the corresponding digital information can be compared with the printed information. The authenticity of the message is guaranteed using RSA digital signatures and a secure DNS implementation based on DANE and DNSSEC for the certificate distribution. A proof of concept was implemented using the ISC BIND DNS Server and OpenSSL to create and distribute the certificates and a Telegram Bot for signature verification.